2021
DOI: 10.32890/ijbf2021.16.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Market Timing Ability of Mutual Fund Houses in Emerging Countries

Abstract: The paper investigates the selectivity and market timing ability of fund houses in emerging countries. The study uses comprehensive performance models on fund houses from four emerging countries. Data span is from 2007 to 2018. Findings indicate that fund managers benefit from the common facilities provided by the fund houses like market research, diversification and investment opportunity. Fund houses showed good selectivity skills but poor market timing ability. The possible reason is that fund houses manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Mutual fund size influences its performance because it relates to the market capitalization portion (Ayu & Asriwahyuni, 2017), and positively affect the mutual fund's performance (Pratama & Wirama, 2018). The large fund quantity can create less company risk and vice versa (Elton et al, 2014), can diversify some assets (Budiono & Musdalifah, 2020), can increase the fund's performance (Bani Atta & Marzuki, 2021), and optimize expected return (Lailiyah & Setiawan, 2020). H3: Mutual fund size positively affects the mutual fund's performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutual fund size influences its performance because it relates to the market capitalization portion (Ayu & Asriwahyuni, 2017), and positively affect the mutual fund's performance (Pratama & Wirama, 2018). The large fund quantity can create less company risk and vice versa (Elton et al, 2014), can diversify some assets (Budiono & Musdalifah, 2020), can increase the fund's performance (Bani Atta & Marzuki, 2021), and optimize expected return (Lailiyah & Setiawan, 2020). H3: Mutual fund size positively affects the mutual fund's performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, a fund size with few assets under management is called small funds and this fund can invest in small stocks called "small-cap funds" (Chen et al, 2004). Fund size can increase the equity fund performance (Bani Atta & Marzuki, 2021), but it could decrease mutual fund performance (Agustin et al, 2022) at the same time. As a disruption factor, Covid-19 increased liquidity risk and reduced return (Szymczyk et al, 2022), and identified that Covid-19 cannot moderate the effect of market timing on equity fund performance (Ariswati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%